Voice or silence: antecedents of whistleblowing intentions. Issue 2 (19th March 2021) - Iwai, Tatiana; Yeung, Luciana; Artes, Rinaldo
Abstract : Purpose: This study aims to examine the effects of peer ethical behavior and individual differences in valuation of fairness vs loyalty on whistleblowing intentions in academic settings. This study also tests the underlying mechanism responsible for the effects of peer behavior on reporting intentions, namely, fear of reprisal. Design/methodology/approach: A survey was conducted with 947 undergraduate students. The model was tested using ordinary least squares regression models followed by bootstrapped mediation analyses. Findings: Results showed that the effects of peer ethical behavior on whistleblowing intentions are mediated by fear of retaliation. Moreover, the findings indicated that, for low-severity transgressions, there is an interactive effect between fear of retaliation and endorsement of fairness over loyalty on whistleblowing intentions. Research limitations/implications: When the misconduct is seen as minor, a potential whistleblower may understand that the expected costs outweigh the possible benefits of blowing the whistle. In such situations, higher fear of retaliation would undermine the effects of individual's endorsement of fairness over loyalty on reporting intentions. Practical implications: As the social environment significantly affects someone's whistleblowing intentions, there should be visible efforts to improve and to foster an ethical infrastructure in organizations. Social implications: As fear of retaliation by peers is one of the most important determinants affecting the decision to report misconduct in general, there must be serious efforts from leaders to mitigate any threat of retaliation to those who come forward. Originality/value: This work contributes to the discussion about individual and situational antecedents of whistleblowing. More importantly, it sheds light on one potential boundary condition for the influence of the fairness–loyalty tradeoff on whistleblowing decisions: severity of the transgression. The findings provide initial evidence that, for low-severity transgressions, fear of retaliation weakens the positive effects of one's moral compass in terms of preference for fairness over loyalty on whistleblowing intentions.